Dickkopf Proteins and Their Role in Cancer: A Family of Wnt Antagonists with a Dual Role - Irina Giralt; Gabriel Gallo-Oller; Natalia Navarro; Patricia Zarzosa; Guillem Pons; Ainara Magdaleno; Miguel F. Segura; José Sánchez de Toledo; Lucas Moreno; Soledad Gallego; Josep Roma (Pharmaceuticals, 2021)
The Wnt signaling pathway regulates crucial aspects such as cell fate determination, cell polarity and organogenesis during embryonic development. Wnt pathway deregulation is a hallmark of several cancers such as lung, gastric and liver cancer, and has been reported to be altered in others. Despite the general agreement reached by the scientific community on the oncogenic potential of the central components of the pathway, the role of the antagonist proteins remains less clear. Deregulation of the pathway may be caused by overexpression or downregulation of a wide range of antagonist proteins. Although there is growing information related to function and regulation of Dickkopf (DKK) proteins, their pharmacological potential as cancer therapeutics still has not been fully developed. This review provides an update on the role of DKK proteins in cancer and possible potential as therapeutic targets for the treatment of cancer; available compounds in pre-clinical or clinical trials are also reviewed.